2023
DOI: 10.55981/aij.2023.1203
|View full text |Cite
|
Sign up to set email alerts
|

Dose Evaluation of Head and Neck Cancer IMRT Treatment Planning Based on Gamma Index Analysis of Varian Halcyon 2.0 Linac

Abstract: Varian Halcyon 2.0 linear accelerator was launched and became available for clinical use in 2018. Therefore, it is necessary to evaluate the accuracy of exit fluence of the Halcyon 2.0 for quality assurance (QA) of head and neck cancer treatment planning, pretreatment, and treatment. The accuracy of the exit fluence for twenty treatment plannings has been evaluated by conducting gamma analysis for QA pretreatment and treatment in each field and composite field by using criteria for gamma index 3 %/3 mm and 2 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…This is in line with Inui's study of prostate cases, with subjects without changes in GPR and subjects with major changes [31]. In addition, Purwati, Suhaimi [32] research by in cases of the nasopharynx showed a dominant decrease in GPR during treatment. The nasopharyngeal case exhibited a decrease in the GPR value faster than the cervical and breast cases as explained in figure 1.…”
Section: Discussionsupporting
confidence: 85%
“…This is in line with Inui's study of prostate cases, with subjects without changes in GPR and subjects with major changes [31]. In addition, Purwati, Suhaimi [32] research by in cases of the nasopharynx showed a dominant decrease in GPR during treatment. The nasopharyngeal case exhibited a decrease in the GPR value faster than the cervical and breast cases as explained in figure 1.…”
Section: Discussionsupporting
confidence: 85%